Ats Hybrid System With Plts And Pln Power For Iot Based Hydroponic Pumps - Indrianto Nugroho; Jamaaluddin (Procedia of Engineering and Life Science, 2021)
Science and Technology for Hydroponics can be use in a limited land areas . This Hydroponic System uses a pump load to drain water continuously using PLN power and result in a waste of electricity costs. therefore this study applies a Hybrid ATS (Automatic Transfer Switch) System using PLTS power and PLN power for pump loads that drain water continuously using internet of things technology so that it can be monitored at any time. The ATS System performs Automatic Switching (disconnect flow a electric) If the PLTS power less than <10V and connects PLN power so that that the pump load remains on until the PLTS power recovers and the Blynk application sends a notification that the PLTS flow condition is cut off and PLN is connected. Error reading from the INA219 sensor at the voltage output is 0.4 -0.6% and the current is 3.0%. The TDS sensor reads the PPM value of hydroponic water from 08.00 to 18.00 with an average 0f 291.38 PPM.